Determinants of water consumption in tourism lodging sector: The case of kazakhstan - Ramazanova, Makhabbat (2021)
Purpose – The main purpose of the paper is to identify, define and analyze the main variables that determine water consumption in the lodging industry, which usually accounts, on average, between the 6% and 10% of total operational costs. Design/Methodology/Approach – The research is based on a survey questionnaire distributed among lodging managers in summer 2016 in the Shchuchinsk-Burabay resort area (Kazakhstan). The regression model methodology has been used to determine the main drivers of water consumption in the tourism lodging facilities. Findings – The estimations obtained in the regression model reveal that the main determinants of water consumption are the total area of the lodging facility, the pool sizes, the type of accommodation (with a special attention to the sanatoriums sector) and the type of board offered. Our study also concludes that the implementation of water saving initiatives significantly reduces water consumption levels and constitutes an effective tool to minimize lodging water consumption. These results can be useful both for policy makers and accommodation managers to develop water management policies to guarantee water, both in quantity and quality, both for the resident population and for the tourism sector. Originality of research – The study extends the geographical scope of research in tourism-water nexus by focusing on the case of emerging tourist destination, such as Kazakhstan